2021
DOI: 10.3390/genes12081186
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan and Collagen Are Prominent Extracellular Matrix Components in Bovine and Porcine Ovaries

Abstract: The extracellular matrix (ECM) is a major component of the ovarian stroma. Collagen and hyaluronan (HA) are critical ovarian stromal ECM molecules that undergo age-dependent changes in the mouse and human. How these matrix components are regulated and organized in other mammalian species with reproductive characteristics similar to women such as cows and pigs, has not been systematically investigated. Therefore, we performed histological, molecular, and biochemical analyses to characterize collagen and HA in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
3
9
0
Order By: Relevance
“…These results have confirmed the findings of another study demonstrating that older adults have thicker MS capsules [ 11 ]. Moreover, these findings are consistent with those of some studies that highlighted the role of the collagens in various diseases and tissues [ 21 , 22 , 23 ]. Parkes et al [ 21 ] reported the prominent role of collagen and HA in the ECM of ovaries, suggesting their crucial activity for ovarian homeostasis, possibly through signaling events or tissue micromechanism.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results have confirmed the findings of another study demonstrating that older adults have thicker MS capsules [ 11 ]. Moreover, these findings are consistent with those of some studies that highlighted the role of the collagens in various diseases and tissues [ 21 , 22 , 23 ]. Parkes et al [ 21 ] reported the prominent role of collagen and HA in the ECM of ovaries, suggesting their crucial activity for ovarian homeostasis, possibly through signaling events or tissue micromechanism.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, these findings are consistent with those of some studies that highlighted the role of the collagens in various diseases and tissues [ 21 , 22 , 23 ]. Parkes et al [ 21 ] reported the prominent role of collagen and HA in the ECM of ovaries, suggesting their crucial activity for ovarian homeostasis, possibly through signaling events or tissue micromechanism. Numerous reports described the association between the single-nucleotide polymorphism rs12722 and rs13936 in the COL5A1 gene and injuries, such as Achilles tendon pathology, anterior cruciate ligament, and tennis elbow [ 41 , 42 , 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hyaluronan is a peculiar polysaccharide with broad functions. Hyaluronan is involved in many physiological processes such as embryogenesis (56), wound healing (57), ECM organization (58)(59)(60), lubricant in the articular cartilage and synovial fluid (61, 62), mammary gland morphogenesis (63) etc. Hyaluronan, composed of cytosolic UDP-N-acetylglucosamine (UDP-GlcNAc) and UDP-glucuronic acid (UDP-GlcUA) precursors, is produced as a linear chain at the plasma membrane by hyaluronan synthases (HAS1-3), which are glycosyltransferases (64,65).…”
Section: Hyaluronan Hyaluronan and Its Synthesismentioning
confidence: 99%